ANALISIS FINANSIAL BUDIDAYA IKAN DALAM KARAMBA JARING APUNG DI SUNGAI MELAWI KECAMATAN PINOH UTARA KABUPATEN MELAWI (Jurnal Social Economic of Agriculture, 2015)
Aquaculture in Floating Net Cage (FNC) is one of the reliable aquaculture technologies that is used to optimize the utilization of waters on rivers, lakes and reservoirs. The types of fish that is usually preserved in Floating Net Cage are Gold Fish (Cyprinus carpio) and Nile Tilapia (Oreochromis niloticus). Survey method is applied in this research and data sample is drawn from the farmer population of floating net cages in Kecamatan Pinoh Utara. The objective of this study is to determine the financial feasibility of aquaculture with Floating Net Cage (FNC) system. This achieved by considering Net Present Value (NPV), IRR (Internal Rate of Return), Net Benefit-Cost Ratio (B/C Ratio), Analysis of PP (Payback Periods) and Sensitivity Analysis. The result indicates that aquaculture of Nile Tilapia and Gold-Fish with Floating Net Cage (FNC) system was financially significant shown by Net Presents Value (NPV) 227.246.769,84 rupiahs, Internal Rate of Return (IRR) 190,97%, Net Benefit Cost ratio (B/C Ratio) 4,34 and Payback Periods (PP) 0,53 years (6 months 10 days). The sensitivity analysis indicates that if there was an increase in operational costs, the amount should not be more than 304,19% and if there was a decrease in profits, the amount should not be more than 44,11%. Keywords: Financial Analysis, Aquaculture, Floating Net Cage, Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (B/C Ratio).